Functionalization of Bacterial Cellulose Nonwoven by Poly(fluorophenol) to Improve Its Hydrophobicity and Durability - Song, Ji Eun; Silva, Carla; Cavaco-Paulo, Artur M.; Kim, Hye Rim (Frontiers in Bioengineering and Biotechnology, 2019)
The present study aims to improve the hydrophobicity and durability of bacterial cellulose (BC) nonwoven by functionalization with poly(fluorophenol). To this end, laccase was first entrapped onto BC and then used to polymerize the fluorophenol {4-[4-(trifluoromethyl) phenoxy] phenol} in situ. The polymerization of fluorophenol by laccase was confirmed through 1H NMR and MALDI-TOF analyses. The amount of poly(fluorophenol) on BC nonwoven was determined by evaluation of the surface hydrophobicity properties such as water contact angle (WCA), surface energy and water absorption time. After BC functionalization with poly(fluorophenol) (20mM), the WCA increased from 54.5±1.2° to 120±1.5° while the surface energy decreased (11.58±1.4mN/m). X-ray photoelectron spectroscopy (XPS) analysis confirmed an increase in the fluorine content in BC from 5.27 to 17.57%. The findings confirmed the polymerization of fluorophenol by laccase and its entrapment onto a BC nanofiber structure. The durability of the functionalization with poly(fluorophenol) was confirmed by evaluating the washing fastness, tensile strength after washing and dimensional stability. The results indicate that the functionalized BC nonwoven had higher tensile strength (x10 times) and better dimensional stability (30 %) than the non-functionalized material.